Validity and accuracy of impulse-response models for modeling and predicting training effects on performance of swimmers - Busso, T.; Chalencon, S. (Medicine & Science in Sports & Exercise, 2023)
Purpose The aim of this study was to compare the suitability of models for practical applications in training planning.